Parental, Community, and Familial Support Interventions to Improve Children's Literacy in Developing Countries: A Systematic Review. Issue 1 (23rd March 2016) - Spier, Elizabeth; Britto, Pia; Pigott, Terri; Roehlkapartain, Eugene; McCarthy, Michael; Kidron, Yael; Song, Mengli; Scales, Peter; Wagner, Dan; Lane, Julia; Glover, Janis
Abstract : This Campbell systematic review assesses the effectiveness of parental, familial, and community support for children's literacy development in developing countries. The review summarises findings from 13 studies, of which 10 were used for meta‐analysis. Many models are widely used in low‐ and middle‐income countries. These include the provision of libraries (standing or mobile) in many countries including Zimbabwe, Kenya, India and Venezuela; local‐language publishing in, for example, Cambodia, Sri Lanka, and Zambia; literacy instruction outside schools including the teaching of literacy through religious instruction; the distribution e‐readers in countries such as Ghana and Uganda; educational TV and radio; and supporting community members to educate children. There is no rigorous evidence of the effectiveness of most of the models being used by governments and NGOs around the world. The exceptions are educational TV and radio, and supporting community members to educate children. Overall, interventions for parent training and of child‐to‐child tutoring are not effective. Eight out of nine reported outcomes show no significant effects. However, there is considerable variation in the findings, so some approaches may be effective in some contexts. Educational television appears to improve literacy with frequent viewing, i.e. three to five times a week, over several months. Abstract: BACKGROUND: For a majority of the world's children, despite substantial increases in primary school enrollment, academic learning is neither occurring at expected rates nor supplying the basic foundational skills necessary to succeed in the 21st century. The significant lag in academic achievement tells us that simply making formal education available does not fully meet children's needs for literacy development. Globally, many interventions are used to support children's literacy development through channels outside of the formal education system, in children's homes or communities. However, there is a lack of information regarding the effectiveness of these interventions. OBJECTIVES: The objective of this systematic review was to examine the effectiveness of parental, familial, and community support for children's literacy development in developing countries. This review provides information about the contextual influences of parental, familial, and community support on children's literacy development skills through the use of interventions that target those influences. We explored the following questions: What models of reading and literacy learning programs have been implemented in homes and communities in low‐ and middle‐income countries (LMICs)? What models of reading and literacy learning programs implemented in homes and communities in LMICs have empirical evidence regarding their level of effectiveness? How effective are these models in improving children's literacy outcomes? SEARCH METHODS: Searches for academic literature were conducted in 15 online databases from across the disciplines of anthropology, economics, education, international relations, political science, psychology, and sociology. To capture gray literature, we searched the websites of United Nations agencies, multinational organizations that provide relevant programming, and governmental agencies. For example, we searched the websites of UNICEF, UNESCO, 3ie, J‐PAL, USAID and others. Project staff and advisory panel members identified literature from their own organizations, and reached out to their contacts to ask for grey literature. The search was conducted from May to July, 2013. SELECTION CRITERIA: To be included in this review, studies had to have been published in 2003 or later and include a test of an intervention involving parents, families, or community members with the goal of improving children's literacy development; children ages 3 to 12 years (or "preprimary" or "primary school" age); a comparison group; and they had to take place in an LMIC (according to 2012 World Bank classification). Studies that addressed educational radio were eliminated from consideration because a systematic review of the impact of educational radio already exists (Ho & Thukral, 2009). DATA COLLECTION AND ANALYSIS: Mendeley software was used to manage citations, abstracts, and documents. Abstracts from each database were initially screened by a single reviewer, but in fact many studies were cited in multiple databases and in turn were screened by two or more reviewers. For the studies that passed the screening, two researchers then independently reviewed each to ensure that it met the criteria for inclusion in this review. Thirteen studies were identified for this review. Information was extracted regarding the study setting, process used to form the control or comparison group, independence of the evaluation, outcome measures, attrition, baseline equivalence on child pre‐literacy or literacy learning, descriptions of the treatment and comparison conditions, characteristics of participants and implementers, and statistics required for meta‐analysis where available. Ten studies were included in meta‐analyses. Eight of the studies were cluster randomized or quasi‐experimental trials, where the level of assignment was at the school or district level. For these studies, effect sizes were computed using Hedges' (2007) dT2 effect size assuming equal cluster sample sizes. RESULTS: The initial search of both the academic and gray literature yielded 10, 430 study abstracts. Title and abstract screening resulted in the elimination of 10, 357 studies, and 21 duplicate citations were removed. Of the remaining 52 studies, 3 were eliminated for addressing the topic of educational radio, and 36 for failure to meet our inclusion criteria. This left the 13 studies that were included in this review. These studies fell into three topic areas: educational television, interventions that help parents learn how to support their children's school readiness, and tutoring interventions delivered by peers or other community members. Most of these studies involved interventions to improve school readiness. The three areas of intervention were examined separately, and studies were combined for meta‐analysis in cases where they used the same intervention approach, and had the required statistical information available. Five studies provided effect size estimates for interventions that help parents support their children learning. Three of the five studies reported significant differences in baseline literacy scores. For overall literacy immediately after the intervention, the effect sizes from five studies including a total of 864 children were heterogeneous, with a mean effect of 0.35 and a 95 percent confidence interval that included o [‐0.07, 0.77]. Four studies including a total of 786 children provided information about overall literacy at one‐year follow‐up. These effect sizes were also heterogeneous, with a mean effect of 0.48 and a 95 percent confidence interval that included o [‐0.35, 1.30]. Five studies of child‐to‐child tutoring were included in the meta‐analysis. These studies all reported difficulties in data collection, raising questions about the quality of data included in the evaluation. For the total reading post‐test, the effect sizes from four studies including a total of 1, 779 children were heterogeneous, with a mean of 0.15, and a 95 percent confidence interval that included o [‐0.27, 0.58]. For the beginning reading sub‐test, four studies including 1, 767 children were also heterogeneous, with a mean of ‐0.107 and a 95 percent confidence interval that included 0 [‐0.40, 0.18]. For the letter identification posttest, effect sizes from five studies including 2, 300 children were heterogeneous with a mean of 0.22, and a 95 percent confidence interval that included 0 [‐0.13, 0.57]. For the writing post‐test, five effect sizes including 1, 993 children were heterogeneous, with a mean of 0.27 that was significantly different from 0 (95 percent confidence interval: [0.02, 0.51]). For the follow‐up test of reading achievement, effect sizes from three studies including 1, 407 children were heterogeneous, with a mean effect size of 0.07 and a 95 percent confidence interval that included 0 [‐0.25, 0.39]. For the follow‐up test of writing achievement, effect sizes from three studies including 1395 students were homogeneous with a mean of 0.033 that was not significantly different from zero (95 percent confidence interval: [‐0.10, 0.17]. For the follow‐up test of overall literacy, effect sizes from three studies including 1, 397 children were homogeneous with a mean effect size of 0.06 that was not statistically different from zero (95 percent confidence interval: [‐0.15, 0.26]. AUTHORS' CONCLUSIONS: This review identified four areas where evidence was available regarding the effectiveness of an intervention approach: educational television, educational radio, interventions intended to support parents' ability to develop their children's school readiness, and tutoring (provided by older peers or community members). Educational radio has been addressed elsewhere (see Ho & Thukral, 2009), so it was not considered in this review. Educational television had a positive impact on young children's literacy development if the child viewed the programming three to five times per week (but not at a lower dosage). Interventions intended to support parents' ability to develop their child's school readiness were not found to be effective overall, although they did have some positive effects in some countries. Peer‐led tutoring was found to improve children's school readiness in writing, but not in other areas of literacy. However, this approach did have significant effects across multiple areas of literacy in some country contexts. A tutoring program led by community members resulted in increases in children's literacy. There were several limitations to this review based on the scarcity of empirical studies and their limited focus on just a few interventions. Numerous descriptions of interventions exist, but few contained a study of program effectiveness in reference to a comparison group. We found only one study that addressed an intervention for children ages 7 and older, and found no eligible studies from Latin America. Therefore, we are left with significant gaps in our understanding of what works in LMICs to improve children's literacy outcomes using interventions outside of the formal education system. Plain language summary: The Campbell review in brief: There is a wide range of models for out‐of‐school interventions to improve children's literacy. Most of these models have not been subject to rigorous evaluation. Support to parents and peers has been largely ineffective in improving literacy, though it has worked in some places. Educational TV has positive effects. What did the review study?: For a majority of the world's children academic learning is neither occurring at expected rates nor supplying the basic foundational skills necessary to succeed in the 21st century. This review examines the availability of evidence and its findings about the effectiveness of interventions to improve parental, familial, and community support for children's literacy development in developing countries. What is the aim of this review?: This Campbell systematic review assesses the effectiveness of parental, familial, and community support for children's literacy development in developing countries. The review summarises findings from 13 studies, of which 10 were used for meta‐analysis. What studies are included in this review?: Included studies were published since 2003 with a test of an intervention involving parents, families, or community members with the goal of improving the literacy of children aged 3 to 12 years. The study design had to have a comparison group, and report literacy‐related outcomes. Thirteen studies are included in the review, covering educational television, interventions that help parents learn how to support their children's school readiness, and tutoring interventions delivered by peers. What are the main results in this review?: What models of reading and literacy learning programs have been implemented in homes and communities? Many models are widely used in low‐ and middle‐income countries. These include the provision of libraries (standing or mobile) in many countries including Zimbabwe, Kenya, India and Venezuela; local‐language publishing in, for example, Cambodia, Sri Lanka, and Zambia; literacy instruction outside schools including the teaching of literacy through religious instruction; the distribution e‐readers in countries such as Ghana and Uganda; educational TV and radio; and supporting community members to educate children. What models of reading and literacy learning programs implemented in homes and communities in LMICs have empirical evidence regarding their level of effectiveness? There is no rigorous evidence of the effectiveness of most of the models being used by governments and NGOs around the world. The exceptions are educational TV and radio, and supporting community members to educate children. How effective are these models in improving children's literacy outcomes? Overall, interventions for parent training and of child‐to‐child tutoring are not effective. Eight out of nine reported outcomes show no significant effects. However, there is considerable variation in the findings, so some approaches may be effective in some contexts. Educational television appears to improve literacy with frequent viewing, i.e. three to five times a week, over several months. What do the findings in this review mean?: There are serious gaps in our knowledge. Programs that have worked in some settings should be replicated elsewhere so the contextual factors for success can be identified and understood. There is no evidence for most models used by governments and NGOs, none from one Latin America, and just one study presenting evidence of effects on children aged over seven. How up to date is this review?: The review authors searched for studies published until July 2013. This Campbell Systematic Review was published in March 2016. What is the Campbell Collaboration?: The Campbell Collaboration is an international, voluntary, non‐profit research network that publishes systematic reviews. We summarise and evaluate the quality of evidence about programs in social and behavioural sciences. Our aim is to help people make better choices and better policy decisions. About this summary: This summary was prepared by Howard White (Campbell Collaboration) based on the Campbell Systematic Review 2016:4 'Parental, Community, and Familial Support Interventions to Improve Children's Literacy in Developing Countries: A Systematic Review' by ET Spier, PR Britto, T Pigott, E Roehlkapartain, M McCarthy, Y Kidron, M Song, P Scales, D Wagner, J Lane and J Glover. Anne Mellbye (R‐BUP) designed the summary, which was edited and produced by Tanya Kristiansen (Campbell Collaboration).